1992
DOI: 10.1016/0165-2427(92)90070-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dexamethasone-induced immunosuppression on the development of faecal antibody and recovery from and resistance to rotavirus infection

Abstract: Rotavirus-naive and rotavirus-immune gnotobiotic calves were treated with high doses of dexamethasone (DX) to suppress the immune system. Calves were then infected with a virulent rotavirus inoculum, J-160, to investigate the role of immune responses both in recovery from primary rotavirus infection and in resistance to secondary rotavirus infection. Treatment of calves with DX markedly suppressed in vitro responsiveness of peripheral blood lymphocytes to mitogens within 48 h of the start of DX treatment. Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1993
1993
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Despite this, a lower amount of antibodies to M. hyopneumoniae was produced in vitro at Days 23 and 25 and the time to reach the peak response to the primary immunization was delayed in the ACTH-treated animals, no differences between the groups were seen in their in vitro or in vivo responses to the second immunization. These results agree with those of Oldham and Bridger (1992), who demonstrated that the time at which dexamethasone (DX) was administered to calves in relation to rotavirus infection was decisive as to the effect it had on their antibody production. When DX treatment started after primary, but before secondary, infection the systemic and local responses were not affected while they were inhibited when the DX treatment commenced prior to the primary infection.…”
Section: Discussionsupporting
confidence: 91%
“…Despite this, a lower amount of antibodies to M. hyopneumoniae was produced in vitro at Days 23 and 25 and the time to reach the peak response to the primary immunization was delayed in the ACTH-treated animals, no differences between the groups were seen in their in vitro or in vivo responses to the second immunization. These results agree with those of Oldham and Bridger (1992), who demonstrated that the time at which dexamethasone (DX) was administered to calves in relation to rotavirus infection was decisive as to the effect it had on their antibody production. When DX treatment started after primary, but before secondary, infection the systemic and local responses were not affected while they were inhibited when the DX treatment commenced prior to the primary infection.…”
Section: Discussionsupporting
confidence: 91%
“…2,13,21 The effects of immunosuppression in domestic animals also have been demonstrated under experimental treatment with corticosteroids. 14,16,20 In the present study, no prominent clinical respiratory signs were observed in any BAV-3 infected calves. A high level of BAV-3 was isolated from BAL fluid cells of DM-treated 1.5-month-old infected calves as well as from those of 7-day-old infected calves but no BAV-3 was isolated from 1.5-month-old infected calves.…”
Section: Discussionmentioning
confidence: 75%
“…[17][18][19] It is well known that immunosuppression with corticosteroids influences the immune system and enhances susceptibility to viral infection. 14,20 Distribution of the cells containing heavy and light polypeptide chains of immunoglobulin also has been described in lung tissues from domestic animals. 1,15 CD8ϩ T lymphocytes have been shown to be important for adenovirus type 7 clearance from respiratory tissues in children and BAV-3 in calves.…”
Section: Discussionmentioning
confidence: 99%
“…For example, cow 4 began to show diarrhea and virus shedding during DM treatment. The DM treatment causes deleterious effects on mucosal immune responses as reported previously [16,18] and likely also compromises mucosal immune responses and host resistance to BCV. We gave a large volume of ice water to 2 cows as a stress inducer before inoculation and one of them was also treated with DM before inoculation.…”
mentioning
confidence: 60%